Water Quality of Ikop Lake and Its Peripheral Fish Farms of Manipur, India: A Comparative Assessment - Devi, Thoudam Bidyarani; Devi, Waikhom Mema; Devi, R. K. Rajeshwori (Research Advances in Environment, Geography and Earth Science Vol. 9, 2024)
The present work explores a comparative valuation of the water quality of Ikop Lake which is a freshwater lake of Manipur, India, and its peripheral fish farms. The water quality of the lake and its peripheral fish farms were assessed by examining fifteen different physicochemical parameters for four months, from June to September 2022. The values of the physicochemical parameters of Ikop Lake and its peripheral fish farm show that 33% of the parameters were not statistically different from WHO recommended value and 66% of the parameters (pH, Temperature, COD, T. Hardness, T. Alkalinity, Chloride, Sodium, potassium, Phosphate, and Total coliform) were exceeded from the standard recommended values. Comparison between the values of the absolute t-score of the parameters of Ikop Lake and its peripheral fish farms shows that the farm's water quality is more degraded than lake water.